Deducing the proton energy configuration - Oakley, William S. (International Journal of Scientific Reports, 2016)
Articles published prior to 1994 by various authors indicate a mass energy sequence for the pion, muon, and electron in the ratios 4: 3: 2 respectively with increments of about 35.3 MeV, with the electron “rest mass” energy rotationally relativistic at α-1mec2, 70 MeV. Considering 35.3 MeV rotationally relativistic by α-2/3 (≈ 26.58) extends the sequence to include the proton mass energy at 938 MeV, i.e. 26.58 x 35.3 MeV = 938.274 MeV. This observation leads to describing the proton as a single EM wave propagating in a toroidal path with volume contracted by α and thereby exhibiting unit charge in the far field, and evidencing partial charges in the near field consistent with the UUD quarks of the Standard Model. As with quantum chromodynamics (QCD), over 99% of the proton rest mass is relativistic in nature. A value for the proton radius is obtained within the empirical uncertaintys.